ANALISIS KINERJA KEUANGAN DAN PENGARUHNYA TERHADAP FINANCIAL DISTRESS PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Bayu Putra Suryana, - (2019)
This research is conducted to analyze the influence of liquidity, leverage and profitability in predicting the occurrence of financial distress at mining company listed in Indonesia Stock Exchange (IDX) period 2015-2017. The technique of determination of the sample using the method of purposive sampling (purposive sampling method). The selection of the sample of 47 mining company listed on the Indonesia Stock Exchange in 2015-2017 produce 29 company is acceptable. Data analysis is done using the Microsoft Excel 2016 and hypothesis testing in this study using a Logistic Regression Analysis with the program E-Views 10 and the level of significance is 5%. The results of the test were obtained (1) the liquidity is represented by CR has a not significant negative effect on financial distress, (2) leverage is represented by DAR has a significant positive effect on financial distress, (3) profitability is represented by DAR has a significant negative effect on financial distress.